Seksualny kapitał w wersji publicznej - Steppa, Hanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
The main intention of Samuel Nowak—the author of Sexual Capital—is to define “what the mass media are for men labelling themselves as gay, taking into account various, although always treated collectively, contexts: economic, political and medial”(p. 9). The sub-title of the study, which defines the direction of the whole text, is Wyobrażone wspólnotysmaku i medialne tożsamości polskich gejów (“Imagined Communities of Taste and Medial Identities of Polish Gay Persons”). In the Nowak’s study, important is the evaluation from outside (as viewed by science) and from within (as viewed by proponents of LGBT). The critical review of Sexual Capital is compatible with the structure of the original text: originally focuses on scientific theories in order to end with the examples from Polish medial realities.